Merek Pribadi, Kepercayaan dan Kesadaran Merek pada Tako.ID - Ari fitra ramadan; Muhamad Iksan (JURNAL MANAJEMEN MOTIVASI, 2026)
The creator economy increasingly places consumer trust in individuals, making personal branding vital. This study examines the effect of personal branding on trust through brand awareness among Tako.ID content creators. Using a quantitative design, data from 62 creator partners selected through purposive sampling were analyzed with PLS-SEM in SmartPLS. Personal branding positively and significantly influenced brand awareness, while brand awareness positively and significantly affected trust. Brand awareness also significantly mediated the relationship between personal branding and trust (coefficient = 0.362; p = 0.038). Thus, consistent brand recognition converts creators’ personal identities into credibility and audience trust. Keywords: Personal Branding; Brand Awareness; Trust; Creator Economy; Content Creator; Social Media Marketing; Consumer Trust; Tako.ID